Fahr’s syndrome in the elderly - Modesto dos Santos, Vitorino (2025)
Dear Editor: We have read the recent article published by Damián-Mucha et al. in this journal, which addresses the main features of Fahr's disease in an older adult (1). The diagnosis was incidental, based on non-contrast CT scan of the brain performed during the evaluation of an accidental fall, which revealed typical basal ganglia calcifications with lenticular predominance. Due to multiple comorbidities, the patient received multidisciplinary care during 41 days of hospitalization and subsequently remained under specialized home medical care for older adults (1). The authors emphasized the role of comprehensive clinical evaluation, laboratory and imaging tests, and geriatric counseling in providing quality care to these patients (1). In addition, they underscored the main features of Fahr's disease: progressive neurological dysfunction, basal ganglia calcifications, absence of endocrine or mitochondrial changes, toxins, or trauma, and no family history of autosomal dominant inheritance (1). Therefore, the following comments aim to highlight the importance of the referenced article.